End‐of‐life care needs for noncancer patients who want to die at home in South Korea. Issue 2 (23rd January 2020) - Lee, Jong‐Eun; Lee, Jiwon; Lee, Hanul; Park, Jin‐Kyoung; Park, Younghye; Choi, Whan Seok
Abstract: Aim: The awareness for the need for end‐of‐life care has increased among noncancer patients. However, studies on the topic have rarely targeted the needs of noncancer patients who want to die at home. This study assessed the end‐of‐life care needs of noncancer patients who were receiving care and wanted to die at home. Methods: A cross‐sectional study design was used and involved 200 participants who were diagnosed as noncancer patients and receiving home care nursing. Data were collected on demographics, disease, Palliative Performance Scale (PPS) scores, and end‐of‐life care needs, in April and May, 2016. Results: Among the six areas of care, "supporting fundamental needs" of patients required the most care, followed by "coordination among family or relatives." Multivariate analysis revealed that the duration of home care nursing held a significant association with end‐of‐life care needs. Conclusion: By reflecting on the comprehensive care needs of patients with chronic illnesses and including them in the care process, it will be possible to provide better quality palliative care to patients at home in the end‐of‐life stages. SUMMARY STATEMENT: What is already known about this topic? Noncancer patients at the end‐of‐life stage have complex needs and problems that are difficult to solve, compared with cancer patients. Noncancer patients need to receive effective symptom management or sufficient support for satisfactory care. End‐of‐life care is still mainly focused on cancer patients and attention to noncancer patients is lacking. What this paper adds? Among the six areas of care, "supporting fundamental needs" of patients required the most care, followed by "coordination among family or relatives." Duration of home care nursing and an income level were significantly associated with higher end‐of‐life care needs. The implications of this paper: Home care nurses must clearly assess the care needs of noncancer patients at the end‐of‐life stage and subsequently provide comprehensive patient‐centered care based on this assessment. It is important to adjust the care direction between patient, family, and medical staff from early on for patients who want to die at home. The results highlight needs for the development of interventions that focus on the duration of home care nursing of patients.